Sustainable poultry education for undergraduate students - A.C. Fanatico; A․Kollanoor Johny; A. Upadhyay; S.B. Bramall (Poultry Science)
Sustainable poultry production can help address many critical socio- and environmental issues, including food insecurity, climate crisis, and loss of biodiversity. The education of undergraduate students in poultry science helps prepare a future workforce in poultry production and to develop responsible citizens for global engagement.The University of Connecticut has a poultry project, funded by U.S. Department of Agriculture's Sustainable Agriculture Systems, that researches the sustainability of meat chickens, particularly holistic health and alternatives to antibiotics. The project's education component is led by the Sustainable Development Department at Appalachian State University in partnership with the Universities of Connecticut, Minnesota, and Arkansas. Educational objectives of the project include 1) help define sustainability in poultry production and prepare instructional materials; 2) provide theory-based undergraduate education with a sustainable poultry course; 3) integrate practice-based innovative approaches using experiential methods, and 4) increase engagement in learning, particularly with international perspectives.As a result of this grant, the project team has developed materials, incorporated topics into existing courses, and created a new course on sustainable poultry production. Instructors use rigorous debate in classes to explore ecology in the environment, human rights in society, and the sustainable use of resources. The team has used university farms for hands-on teaching, and traveled to India to work with international collaborators and students.Graduates are engaged citizens who can be part of community-based food systems, help poultry companies address sustainability issues, and provide a global perspective for sustainable development.